Literary Analysis Of “The Kitchen God’s Wife” By Amy Tan - Matyokubova Shukurjon Farhodovna (Genius Journals, 2022)
Amy Tan’s “The Kitchen God’s Wife” is a readily recognizable successor to her first book, the 1989 bestseller “The Joy Luck Club”. It is cast in the same thematic, substantive, and stylistic mold. Unlike “The Joy Luck Club”, however, which assumed the form of a cycle of related short stories revolving around four mothers and their four daughters, “The Kitchen God’s Wife” is a full-fledged novel. Like its predecessor, “The Kitchen God’s Wife” is Chinese American and generational in subject and feminist in perspective: Its point of departure is the lack of communication between mother and daughter, a mother who is a Chinese American immigrant and a daughter who is American born, but its scene quickly shifts from California to China, and the orbit of its pathos broadens to include the ugly husband-wife relationship that the mother had with her first husband.
Keywords: Individuality; humor; irony; mother and daughter